Understanding Diaspora: Home and Overlapping Hyphenation in The Shadow Lines (Spectrum, 2023)
The idea of an imaginary homeland and the adopted country is at the heart of diasporic discourse. There is a continuous struggle on the part of the diasporas about the donor culture and the recipient culture which creates an ambivalence, separation anxiety over dislocation, as well as, an existential crisis. The apparent solution to this problem seems to lie either in shading off one’s individuality as an ex-colonized and eventually becoming westernized or retaining the “desh” in him/her while appropriating the diasporic state. However, the more they try to assimilate or acculturate themselves, the more they feel alienated from the recipient culture. Thus, they posit a “Trishanku” position and because of their peculiar positionality, they try to transcend time and space with the wings of memory to experience the lost past which they call ‘home’. This paper takes Amitav Ghosh’s The Shadow Lines into consideration and explores how different characters in this novel harbor different notions of home and how they come to terms with their hyphenated position in a transcultural space. This will be achieved through the trajectories of two of its main characters: Tha’mma and Ila. For them, the diaspora home becomes a problematic site, and there is a silent clash in their ideologies. This paper shows that it is more so because the sense of self/existence is shaped by the social relations determined by the collective history, class, race, gender and, most importantly, by culture. Thereby, the characters’ concept of a home remains a prolonged paradox.Spectrum, Volume 17, June 2022: 66-74